Corporate strategy : a resource-based approach - Collis, David J.; Montgomery, Cynthia A. (Boston, Mass. : McGraw-Hill/Irwin, 2005)
The book is founded upon established research traditions. In particular a number of insights are drawn from two distinct bodies of research: the resource-based view of the firms, which has gained prominence in the field of strategic management; and organizational economics, in particular transactions cost analysis and agency theory. Both of these theoretical traditions have made a substantial contribution to the arguments advanced here. Also included in the book is a substantial amount of materials that is not available elsewhere. Most important, it introduces a unique approach to corporate strategy that the authors have developed over many years of research, teaching and consulting on the topic.
Includes index.
rpm 10/07/13
Loans
Keywords: Organizational effectiveness; Strategic planning